Problematika Pendanaan Aset Danantara terhadap Rencana Investasi Negara - Sebastian Alboen Sihombing; Reva Setianingsih; Urai Vidia; God Godsent (Jurnal Hukum, Administrasi Publik dan Negara, 2025)
This study aims to analyze the effectiveness of funding sourced from Danantara—a digital platform that manages state investment with funding support from state-owned bank customers—in supporting the acceleration of national development. In the context of state investment, collaboration between the Investment Management Institution (LPI) and state-owned financial institutions is important as a form of fiscal innovation and expansion of non-APBN financing sources. The method used is a qualitative descriptive approach with literature studies from various scientific journals and related laws and regulations. The results of the study show that Danantara has the potential to be a reliable, flexible, and sustainable long-term funding instrument. Through funds collected from state-owned bank customers, state investment can be focused on strategic sectors such as infrastructure, energy, and digitalization. However, its effectiveness is still faced with regulatory challenges, transparency of governance, and public literacy regarding state investment mechanisms. For this reason, it is necessary to strengthen regulations and synergy between financial institutions, as well as increase public trust so that Danantara can function optimally as the main supporter in realizing fiscal independence and national economic growth.